A Cytochemical Study on the Pancreas of the Guinea Pig : VI. Release of Enzymes and Ribonucleic Acid from Ribonucleoprotein Particles - Siekevitz, Philip (The Rockefeller University Press, 1960)
Ribonucleoprotein (RNP)(1) particles isolated by DOC treatment from pancreatic microsomes have a RNA content of 35 to 45 per cent of their dry weight. In the analytical ultracentrifuge about 85 per cent of the material has a sedimentation coefficient of ∼85 S. These particles contain amylase, RNase, and trypsin-activatable proteolytic activities which cannot be washed off or detached by incubation in 0.44 M sucrose. The enzymes are released, however, by incubation in the presence of low concentrations of ATP, PP, or EDTA, and high concentrations of IP and AMP. At the same time, and at the same concentrations, ∼80 per cent of the RNA and ∼25 per cent of the protein of the particles becomes also non-sedimentable. The simultaneous addition of Mg(++) to the incubation medium prevents these losses. This finding, together with the observation that all the Mg(++) of the particles is released by the same agents, makes it likely that Mg(++) holds the particles together, and that its removal by the chelators used causes the particles to disintegrate. These findings are discussed in relation to the molecular structure of the RNP particles.